2022
DOI: 10.5603/fm.a2021.0080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gender differences on pyriform aperture of human skulls using geometric morphometric method

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The results of studies conducted on a sample of skulls from the Bosnian population showed the existence of sex differences on different parts of the skull with the application of different methodologies [51][52][53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies conducted on a sample of skulls from the Bosnian population showed the existence of sex differences on different parts of the skull with the application of different methodologies [51][52][53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Cranial measurements have strong sex discriminating power. The nasal bone is less in breath in females [11][12][13][14][15]. In many studies, the main focus is on the glabellar region; a new quantitative method is used to estimate frontal inclination for sex determination.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative methods are based on measuring linear diameters on skeletal remains or on CT scans, as well as radiographic images of skeletal remains or part of skeletal remains. (Sarac-Hadzihalilovic et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Franklin et al (2006) in their study conducted on the crania of indigenous southern Africans used geometric morphometrics method for analysis of sexual dimorphism. Sarac-Hadzihalilovic et al (2021) used geometric morphometrics method for analysis of sex differences on piriform aperture of human skulls.…”
Section: Introductionmentioning
confidence: 99%